FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT PRODUKSI PETANI GARAM DI DESA KUSAMBA, KECAMATAN DAWAN, KABUPATEN KLUNGKUNG - Suryawan, I Nyoman Putra; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 9 (2023): Vol.12.No.9.SEPTEMBER. 2023[586-649]DO - 10.24843/EEP.2023.v12.i09.p02, 2023)
During the process of producing salt, some farmers will concentrate on factors that have an impact on production. As a result, the focus of this study will be on determining the factors that influence salt production. Based on the responses to a survey via questionnaire, observations, and in-person interviews with 62 participants, the research data source was compiled. The kind of examination procedure applied in this study is utilizing a quantitative investigation strategy with different relapse types. This study demonstrates that farmers in Kusamba Village's salt production levels are correlated with capital, labor, and land area. Keyword : capital, Labor, Land Area, Production Rate